The Role of Time Availability in Moderating Hedonic Shopping Motivation toward Impulse Buying of Consumer Online at Harbolnas's Event - Maqhfiroh, Lailatul; Prihandono, Dorojatun (Management Analysis Journal, 2019)
This study aims to examine the influences of hedonic shopping motivation toward online impulse buying on online customers online shop at Harbolnas event which time availability as moderating variable. Hedonic shopping motivation in this research are categorized into five categories whice are adventure shopping, social shopping, relaxation shopping, idea shopping and value shopping. The object of this study is customer online shop who were followed and bought product on Harbolnas event. This method of this study is quantitative research by using survey, with the sample size of one hundred and ten people who often make online purchase on Harbolnas event. The technique for sample selection is using non probability sampling with the type of purposive sampling. The data were collected by using questionnare with Likert scale. The method for data analysis is SEM ( Structual Equation Modeling) with PLS ( Partial Least Square). The results showed that hedonic shopping motivation has positive and significant influence toward impulse buying. However adventure shopping, social shopping and idea shopping has negative and not significant influence toward impulse buying. Time availability has not moderated relation between hedonic shopping motivation toward impulse buying.